Rekomendasi Penentuan Siswa Berprestasi Dengan Menggunakan Metode Pembobotan PIPRECIA dan Weighted Sum Model - Permata; Aditya Lapu Kalua (PT. Tech Cart Press, 2024)
Outstanding students are those who stand out in various academic as well as non-academic aspects. They not only have high achievements in terms of grades or exams, but also show dedication and perseverance in pursuing their interests and talents. One of the problems in the selection of outstanding students is the potential for bias and injustice. Non-transparent assessment processes or unclear criteria can lead to inequalities in opportunities for students to be recognized for their achievements. This study aims to develop a recommendation system that can assist schools or educational institutions in identifying and supporting outstanding students effectively, based on a structured and measurable approach using PIPRECIA weighting methods and WSM (Weighted Sum Model). In determining outstanding students, the use of a combination of PIPRECIA and WSM weighting methods can be an effective approach. The first step is to use the PIPRECIA method to establish the relative priorities of various assessment criteria. Once the weight of the criteria is established, WSM is used to assess each student based on the criteria that have been identified. The results of the ranking of outstanding students showed that students on behalf of Yulistio with a WSM score of 50.163 got 1st place, then students on behalf of Annisa with a WSM score of 49.95 got 2nd place, and finally students on behalf of Ferdian with a WSM score of 49.039 got 3rd place.